Performance analysis of coroutines and other concurrency techniques in Kotlin language for I/O operations - Grabowiec, Michał; Wiktor, Sebastian; Smołka, Jakub (Journal of Computer Sciences Institute, 2024)
This article focuses on analyzing the performance of coroutines and other concurrent processing techniques in Kotlin language for input/output operations. For this purpose, coroutines, traditional threads, thread pool and virtual threads were put together. An appropriate application was created and test scenarios were developed. A series of tests were conducted, followed by an analysis of the obtained results. These results indicate that coroutines and thread pool exhibit the highest performance, highlighting their importance in optimizing concurrent processing in the Kotlin language.